Flawless consulting : a guide to getting your expertise used - Block, Peter, 1939- (Wiley, 2023)
"The fundamentals of the flawless consulting process have not changed. Through a step-by-step walk through of the five phases of consulting: Entry and Contracting, Discovery and Dialogue, Analysis and Decision to Act, Engagement and Implementation, and Extension, Recycle or Termination, Peter Block will engage in a deeper and contemporized discussion of the skills and behavior required for success. For example, there is new attention to convening skills, to the importance and process for peer contracting, and to questions to take the consultant/client relationship to a deeper level. As in previous editions, Block will tell the reader exactly what to say and how to act to consult flawlessly at each stage of the process. The 4th edition will feature: ? Restructuring the chapter on the contracting meeting into three shorter, more digestible chapters to make them easier to navigate and put into practice depending on how the consulting project was initiated (Asked In, Sent In, Want In) ? A new chapter titled ?Being Right??Really? giving more attention to the interpersonal aspect of the relationship consultants have with the client and exploring a set of beliefs about relationships, learning, and the nuances of how change occurs that ultimately define the consultant?s practice. ? A new chapter titled ?The Internal Consultant?s Dilemma? offering additional depth and nuance on recommended ways for internal consultants to consult flawlessly ? A separate chapter on virtual consulting skills titled ?The Technology: A Marriage of Reality and Myth,? which speaks to how to manage the business of the flawless consulting phases if you are never in the same room with anyone and how to humanize virtual engagements. ? Expanded, deeper discussion in the last chapter of ?The Final Question Is One of Faith,? the idea being that practicing flawless consulting is counter cultural and it can take an act of courage to change the conversations along the way"--